Fabrication of an effusive molecular beam instrument for surface reaction kinetics - CO oxidation and NO reduction on Pd(111) surfaces - Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Catalysis Letters, 2007)
A simple molecular beam instrument (MBI) was fabricated for measuring the fundamental parameters in catalysis such as, sticking coefficient, transient and steady state kinetics and reaction mechanism of gas/vapor phase reactions on metal surfaces. Important aspects of MBI fabrication are given in detail. Nitric oxide (NO) decomposition and NO reduction with carbon monoxide (CO) on Pd(111) surfaces were studied. Interesting results were observed for the above reactions and they support the efficiency of the MBI to derive the fundamental parameters of adsorption and catalysis. Sustenance of CO oxidation at 400 K is dependent mostly on the absence of CO-poisoning; apparently, CO + O recombination is the rate determining step <= 400 K. NO adsorption measurements on Pd(111) surface clearly indicating a typical precursor kinetics. Displacement of the chemisorbed CO by NO on Pd(111) surfaces was observed directly with NO + CO beams in the transient kinetics. It is also relatively easy to identify the rate-determining step directly from the MBI data and the same was demonstrated for the above reactions.
Keywords: carbon monoxide; catalysis; kinetics; molecular beam; nitric oxide; Pd(111)

Electronic decoupling of surface layers from bulk and its influence in oxidation catalysis: a molecular beam study - Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Applied Surface Science, 2009)
Interactions between oxygen and Pd-surfaces have important implications, especially towards oxidation reactions, and influence of subsurface oxygen to oxidation reactions is the focus of the present study. In our efforts to understand the above aspects, CO oxidation reactions have been carried out with mixed molecular beam (MB), consisting CO and O(2), on Pd(1 1 1) surfaces under a wide variety of conditions (T = 400-900 K, CO: O(2) = 7: 1 to 1: 10). A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd subsurface layers, and its significant influence towards CO oxidation at high temperatures (>= 600 K). Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(O-sub)), above which the reactive CO adsorption occurs on the surface and simultaneous CO(2) production begins. There is also a significant time delay (G) observed between the onset of oxygen adsorption and CO adsorption (and CO(2) production). Above studies suggest an electronic decoupling of oxygen covered surface and subsurface layers, which is slightly oxidized, from the metallic bulk, which induces CO adsorption at high temperatures and simultaneous oxidation to CO(2). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic decoupling; heterogeneous catalysis; molecular beam; Oxidation; Pd(111); Subsurface diffusion

Kinetic evidence for the influence of subsurface oxygen on palladium surfaces towards CO oxidation at high temperatures - Gopinath, Chinnakonda S.; Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan (Chemistry-an Asian Journal, 2009)
Transient state kinetics of the catalytic oxidation of CO with 0, on Pd-surfaces has been measured under isothermal conditions by using a molecular beam approach. Systematic studies were carried out as a function of reaction temperature and CO+O(2) composition. With sufficient kinetic evidence, we have demonstrated the positive influence of subsurface oxygen towards CO-adsorption and oxidation to CO, at high temperatures (600-900 K) on Pd-surfaces, and the likely electronic nature of the surface changes with oxygen in the subsurface. These studies also provide a direct proof for CO-adsorption with a significantly reactive sticking coefficient at high temperatures on Pd-surfaces exhibiting a significant subsurface O-coverage.
Keywords: Adsorption; kinetics; Oxidation; Palladium; surface analysis

Nitric oxide reduction with ethanol on palladium surfaces: a molecular beam study - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S.; Counsell, Jonathan; Gilbert, Lee; Bowker, Michael (Journal of Physical Chemistry C, 2009)
Nitric oxide (NO) reduction with ethanol has been carried out with molecular beam instruments in order to understand the influence of ethanol blended gasoline on NO reduction. Maximum NO reduction and nitrogen production was observed between 500 and 600 K. Oxidation products, CO, CO(2), and H(2)O were also observed. Beam switching experiments have been performed between fuel-rich and fuel-lean compositions to demonstrate that the NO reduction can be managed under net oxidizing conditions on Pd surfaces. Nitrogen production only occurs transiently on the relatively clean Pd surface in the oxygen-rich condition due to slow build up and blockage of the reaction by surface oxygen atoms. This shows the need to maintain relatively oxygen free surfaces to manage NO reduction under net-oxidizing conditions by beam oscillation between fuel-rich and fuel-lean compositions.

Revisit to carbon monoxide oxidation on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
Carbon monoxide (CO) oxidation on Pd(111) surfaces has been studied by molecular beam methods with mixed molecular beams (CO + O(2)) between 400 and 900 K and a CO:O(2) ratio of 7:1 to 1:10. A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd(111) subsurface layers and its significant influence toward CO oxidation at high temperatures (>= 600 K). An overall influence of subsurface oxygen on the kinetics of the CO oxidation reaction is addressed. Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(Osub)), above which the reactive CO adsorption occurs on the surface with subsequent CO(2) production. The above observation Was demonstrated with CO-rich reactant compositions (CO + O(2)) above 600 K via instant oxygen adsorption on Pd surfaces; however, onset of CO adsorption as well as CO(2) production occurs after a time delay. theta(Osub) and the time delay in CO adsorption (and CO(2) production) increase with increasing temperature and with CO-rich compositions. theta(Osub) was measured up to 0.3 monlayer (ML) between 500 and 850 K before the onset of CO adsorption; however, theta(Osub) increases from an insignificant value at <500 K to 0.4 ML at 900 K with a pure O(2) beam. Onset of CO adsorption with a significant sticking coefficient on the Pd surfaces, that is, covered with significant subsurface oxygen, underscores a change in the electronic state of Pd surfaces toward mildly oxidized (or Pd(delta+)), and an electronic decoupling occurs between the bulk and the surface. The jellium model is invoked to demonstrate the changes observed. A similar observation with polycrystalline Pd surfaces suggests the defect sites is one of the channels for oxygen diffusion into subsurfaces. Initial sticking coefficient (s(0)) measurements demonstrate that there is no significant competition between CO and O(2) adsorption from the CO + O(2) mixture between 400 and 600 K, and indeed they are largely independent of each other. The maximum steady-state CO(2) formation rate was observed for a 1:1 CO/O(2) beam composition between 500 and 550 K. However, with a significant theta(Osub) the rate of CO(2) Production in the steady state is considerable even at high temperatures (700-850 K), and a broadening of the active CO oxidation regime to high temperature is observed with O(2)-rich compositions.

Kinetics of nitric oxide adsorption on Pd(111) surfaces through molecular beam experiments: a quantitative study - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S.; Prasad, Sudarsan D. (Journal of Physical Chemistry C, 2011)
A detailed kinetic picture derived by molecular beam studies of the adsorption-desorption of the NO/Pd(111) system is presented. Numerical simulations and detailed kinetic analysis show that the precursor state model of adsorption provides a valid picture of the sticking coefficient variation with surface coverage, especially at low temperatures. At higher temperatures, the precursor model gives way to the Langmuir molecular model of adsorption. All the parameters of the precursor state model have been quantified. Temperature programmed desorption (TPD) studies further show that there is a slight repulsive interaction between adsorbed NO molecules and there is only a negligible fraction of dissociated molecules on the surface for temperatures less than 500 K, as the Pd(111) surface is defect free. A Bragg-Williams (BW) lattice gas model with repulsive interactions, within the framework of mean field approach (MFA), is shown to describe the TPD spectra reasonably well.

Possible deNO(x) management under net oxidizing conditions: a molecular beam study of (NO)-N-15+CO+O-2 reaction on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Isothermal kinetic measurements of (NO)-N-15 reduction with CO on Pd(111) surfaces were carried out under net-oxidizing conditions with (NO)-N-15 + CO + O-2, using a molecular beam instrument (MBI). Transient state (TS) and steady state (SS) kinetic details of the above reaction were obtained for a wide range of temperature and beam compositions, especially with O-2-rich compositions. Increasing O-2 content, generally, suppresses (NO)-N-15 reduction in the SS; nonetheless, irrespective of O-2 content, N-15(2) was produced in TS, and to a significant extent under SS conditions too. Sustainable N-2 production between 450 and 600 K and with low to moderate amount of oxygen was observed, and the extent of NO decomposition was also quantified. The ratio of N-15(2): (N2O)-N-15 was generally found to be around 8:1 under most of the reaction conditions. Maxima in the SS reaction rates of all products were observed between 500 and 600 K. Compared to other elementary reaction steps, a slow decay observed with N + N -> N-2 step under SS beam oscillation conditions demonstrates its contribution to the rate limiting nature of the overall reaction. Fast beam switching experiments have been performed alternately between O-2-lean and -rich conditions, thus highlighting the effectiveness of (NO)-N-15 reduction in TS, irrespective of the beam composition. Possibly in a future technology initiative, this aspect could be exploited to manage more (NO)-N-15 reduction on Pd-based catalysts.